Gravity-driven membrane filtration for water and wastewater treatment: A review. (1st February 2019) - Pronk, Wouter; Ding, An; Morgenroth, Eberhard; Derlon, Nicolas; Desmond, Peter; Burkhardt, Michael; Wu, Bing; Fane, Anthony G.
Abstract: Gravity-driven membrane (GDM) filtration has been investigated for almost 10 years. The technology is characterized not only by relatively lower transmembrane pressures which can be achieved by gravity (extremely low energy consumption), but also by the phenomenon of flux stabilization: A biofilm is allowed to form on the membrane and a stabilization of flux occurs which is related to biological processes within the biofilm layer on the membrane. This enables stable operation during a year or longer without any cleaning or flushing. Initially, the technology was developed mainly for household drinking water treatment, but in the meantime, the research and application has expanded to the treatment of greywater, rainwater, and wastewater as well as the pretreatment of seawater for desalination. This review covers the field from the rather fundamental research on biofilm morphology and microbial community analysis to the impact of feedwater composition, process parameters and organic removal performance. Not only household applications, but also for community-scale treatment and full-scale applications are discussed. In addition, the application potential is highlighted in comparison to conventional ultrafiltration. Finally, an overall assessment is illustrated and the research and development needs are identified. Highlights: Flux stabilization in gravity-driven UF has first been reported in 2010. Many papers have described this process for water and wastewater treatment. Mechanisms of biofilm formation and fouling have been studied. Improved removal of dissolved compounds has been reported. Total costs can be lower than conventional UF, depending on the scale of application.